Bacteriological Profile and Antimicrobial Susceptibility Pattern of Pus Isolates from Tertiary Care Hospital - Fatima, Ambreen; Gohar, Hareem; Dawood, Kamran; Siddiqui, Hira Zafar; Sajjad, Mehwish; Naseem, Saima (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To detect the most frequent bacterial pathogens causing wound infections and monitor their susceptibility profile at a tertiary care hospital in Karachi, Pakistan. Methodology: A retrospective cross-sectional study spanning 12 months from March 2020 to February 2021 was carried out at Patel Hospital Karachi. Wound swabs and pus samples were collected by sterile syringe and using a non-probability consecutive sampling technique from both inpatients and outpatients of all age groups and genders and processed by standard microbiological techniques. Antibiotic sensitivity testing was done using the disk diffusion technique per Clinical and Laboratory Standard Institute (CLSI) guidelines. Results: Among 1000 samples, 725 (72.5%) showed growth, out of which Gram-negative bacteria were 524 (59%), and 359 (41%) were Gram-positive bacteria. Amongst the Gram-positive bacteria, the majority was Methicillin Resistant Staphylococcus aureus (MRSA 76%), followed by Methicillin Sensitive Staphylococcus aureus (MSSA 24%), Streptococcus species (4%) and Streptococcus pneumonia (3%). Vancomycin, Linezolid and Chloramphenicol were the most susceptible antibiotics against Gram-positive organisms. The frequent Gram negative organisms were Pseudomonas aeruginosa (23%), Eschericia. coli (14%), Klebsiella spp (11%) and Acinetobacter baumannii (8%). Most Gram-negative bacteria were susceptible to Amikacin, Meropenem and Piperacillin-tazobactam and Tigecycline. Conclusion: S.aureus and P.aeruginosa were the most identified bacteria in pus samples with varying antibiograms. Growing resistance to beta-lactam antibiotics was a severe concern in the current study. This study helps the physicians about the usual microorganisms encountered in pus samples with prudent prescription of antibiotics. Keywords: Bacteriological Profile, Antimicrobials, Pus, Wound Swabs, Antibiogram, MRSA, CRE